Adecuación de la planta física para la correcta circulación de usuarios en los espacios de interés común al interior del asilo San Antonio en la ciudad de Barranquilla (2019)
This research work consists in the improvement of the infrastructure of a nursing home located in Barranquilla (Atlántico) that guarantees the adequate access and mobility of both users and visitors of the place, after performing an analysis meticulous of the current conditions of these aspects in the facilities of this place. The research was carried out based on the methodology proposed for this case, gathering information from different sources, such as already given researches, description and analysis of the building, surveys made to users, workers and visitors, all this in order to identify the critical elements and thus be able to propose a more optimal design that allows access to users in a comfortable and safe way. That allowed the elaboration of the suggested solutions and conclusions, which were projected in favor of the conditions of the infrastructure and this way to offer a better service to the users of this information. Also, it contributed the accomplishment of a budget analysis of these modifications to orient the asylum for the attainment of economic resources, which if done, would allow the provision of a better service to users, which due to the age, are persons with disabilities that need services in equal conditions without any discrimination or difficulty